Analysis of Agricultural Expansion and Deforestation in the Legal Amazon: A Spatio-Temporal Perspective (1985-2023) in Lucas do Rio Verde-MT - Gulinelli, Érica Lemos; Seabra, Jessica; Ravache, Rosana Lia; Paula, Nátali de (National Journal of City Management, 2024)
Over the past four decades, the exponential growth of agricultural activities in Mato Grosso has led to major changes in land use and land cover. Although environmental legislation was in force, it was only in 2004 that more effective regulatory instruments were implemented to curb deforestation in the Legal Amazon. This study aimed to conduct a spatial-temporal analysis of the municipality of Lucas do Rio Verde, Mato Grosso, considering the impact of land use policies in the Brazilian Legal Amazon on land use dynamics. The time frame covers the period from 1985 to 2023, with data collected via the MapBiomas platform and socioeconomic reports from the Brazilian Institute of Geography and Statistics (IBGE). The results indicate a significant advance in agriculture and the consequent deforestation, especially between 1985 and 1995 motivated by government incentives that promoted migration to the interior of Mato Grosso since the 1970s, offering financing and benefits to stimulate the planting of crops and cattle ranching. The analysis highlights how agricultural use in the Legal Amazon has not only altered the vegetation cover, but has also generated new legislative conflicts over the sustainable use of forests. It is therefore concluded that agricultural activities in the region require continuous monitoring and more robust policies to ensure environmental preservation, in addition to integrated management that combines economic development with the sustainability of forest cover and global climate regulation.
Keywords: Anthropogenic changes; Land cover; Environmental preservation